Advanced Age and Post–Acute Care Outcomes After Subarachnoid Hemorrhage. Issue 10 (24th October 2017) - Fehnel, Corey R.; Gormley, William B.; Dasenbrock, Hormuzdiyar; Lee, Yoojin; Robertson, Faith; Ellis, Alexandra G.; Mor, Vincent; Mitchell, Susan L.
Abstract : Background: Older patients with aneurysmal subarachnoid hemorrhage (aSAH) are unique, and determinants of post–acute care outcomes are not well elucidated. The primary objective was to identify hospital characteristics associated with 30‐day readmission and mortality rates after hospital discharge among older patients with aSAH. Methods and Results: This cohort study used Medicare patients ≥65 years discharged from US hospitals from January 1, 2008, to November 30, 2010, after aSAH. Medicare data were linked to American Hospital Association data to describe characteristics of hospitals treating these patients. Using multivariable logistic regression to adjust for patient characteristics, hospital factors associated with (1) hospital readmission and (2) mortality within 30 days after discharge were identified. A total of 5515 patients ≥65 years underwent surgical repair for aSAH in 431 hospitals. Readmission rate was 17%, and 8.5% of patients died within 30 days of discharge. In multivariable analyses, patients treated in hospitals with lower annualized aSAH volumes were more likely to be readmitted 30 days after discharge (lowest versus highest quintile, 1–2 versus 16–30 cases; adjusted odds ratio, 2.10; 95% confidence interval, 1.56–2.84). Patients treated in hospitals with lower annualized aSAH volumes (lowest versus highest quintile: adjusted odds ratio, 1.52; 95% confidence interval, 1.05–2.19) had a greater likelihood of dying 30 days after discharge. Conclusions: Older patients with aSAH discharged from hospitals treating lower volumes of such cases are at greater risk of readmission and dying within 30 days. These findings may guide clinician referrals, practice guidelines, and regulatory policies influencing which hospitals should care for older patients with aSAH.